2020
DOI: 10.1016/j.drugalcdep.2020.108245
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention and vigilance deficits associated with HIV and a history of methamphetamine dependence

Abstract: Background: Human immunodeficiency virus (HIV)-associated neurocognitive disorders persist in the era of antiretroviral therapy (ART). One factor that is elevated among persons with HIV (PWH) and independently associated with neurocognitive impairment is methamphetamine dependence (METH+). Such dependence may further increase cognitive impairment among PWH, by delaying HIV diagnosis (and thus, ART initiation), which has been posited to account for persistent cognitive impairment among PWH, despite subsequent t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Drug abuse can cause chronic illness 3 ; long-term abuse may also lead to symptoms such as anxiety, depression, insomnia, and impaired social functioning. 4 , 5 , 6 , 7 , 8 Opioid dependence is one of the most severe types of drug dependency. 9 Currently, the treatment of drug dependency relies on drug replacement therapy, in which either methadone or buprenorphine is used to treat opioid addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Drug abuse can cause chronic illness 3 ; long-term abuse may also lead to symptoms such as anxiety, depression, insomnia, and impaired social functioning. 4 , 5 , 6 , 7 , 8 Opioid dependence is one of the most severe types of drug dependency. 9 Currently, the treatment of drug dependency relies on drug replacement therapy, in which either methadone or buprenorphine is used to treat opioid addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Attention is crucial as it affects other cognitive functions such as language, memory, and problem‐solving; it also reflects the complex interplay of multiple independent systems in the brain (Burgoyne & Engle, 2020; Fan et al, 2005; Pessoa et al, 2003). Reduced sustained attention (London et al, 2005; Pocuca et al, 2020; Rubenis et al, 2018) has been reported in previous studies, suggesting that MUD might be associated with sustained attentional deficits. Poor sustained attention is also indicative of limited improvement in motivation during early rehabilitation programs, suggesting its importance in the prediction of treatment outcome (Rubenis et al, 2018).…”
Section: Discussionmentioning
confidence: 63%
“…Reduced sustained attention (London et al, 2005;Pocuca et al, 2020;Rubenis et al, 2018) has been reported in previous studies, suggesting that MUD might be associated with sustained attentional deficits.…”
Section: Differences In Cognitive Profilesmentioning
confidence: 75%
“…Participants were stratified into one of four groups: HIV−/METH−, HIV−/METH+, HIV+/METH− and HIV+/METH+. Exclusion and inclusion criteria have been described in full in previous publications and are described in brief here as well [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%